Effect of an Unbalanced Diet on the Incidence of Cerebrovascular Disorders - Yamashiro, Harumi; Tokuhisa, Fumi (Eiyōgaku zasshi, 2000)
A study was made on 84 individuals who underwent cerebral health screening. The subjects were classified into the following three groups: (1) those in whom no cerebral abnormality was detected (24 individuals, normal group); (2) those with asymptomatic cerebrovascular disorders such as brain infarction and cerebral atrophy (21 individuals, brain disease group); and (3) those without any abnormality in brain function but with other diseases such as hyperlipidemia, hypertension, fatty liver, and diabetes (39 individuals, other disease group). The clinical data for these individuals and the components of their dietary intake were compared. The brain disease group had a higher dietary intake of energy and protein (animal protein in particular) than the other two groups. This tended in this group to be markedly higher with those subjects in their 50s or older. The dietary intake by the other disease group which, although not having cerebrovascular disorders did have the potential risk factors for such disorders, was similar to that by the normal group, being lower in energy and protein than that by the brain disease group. These results show a link between the incidence of cerebrovascular disorders and the ingestion of a high-energy diet that is high in animal protein. The development of cerebrovascular disorders may thus be mitigated by appropriate nutritional management such as by avoiding a high-energy, high-protein diet for those of 50 years and older.